2014
DOI: 10.3390/pharmaceutics6030530
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Commercially Available Vaginal Lubricants: A Safety Perspective

Abstract: Vaginal lubricants are widely used by women to help solve intercourse difficulties or as enhancers, but recent reports raise questions about their safety. Twelve commercially available gel products were tested for pH value, pH buffering capacity, osmolality and cytotoxicity relevant to vaginal delivery. Obtained data were analyzed in light of the recent Advisory Note by the World Health Organization (WHO) for personal lubricants to be concomitantly used with condoms. Results showed that most products do not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…In healthy adults, normal vaginal and rectal pH ranges are 3.8–4.5 and ∼7.0, respectively 30 , and the optimum requirements for both vaginal and rectal intercourse cannot be bridged in a single lubricant. Cunha and colleagues commented that 'outcomes of low pH are even less understood, but animal data suggest that values of 3 or less are unacceptable for human use' 39 . Therefore, clinicians need to be aware that some preparations do not meet this recommendation (see Table 1 ).…”
Section: Characteristics To Consider When Choosing a Personal Lubricamentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy adults, normal vaginal and rectal pH ranges are 3.8–4.5 and ∼7.0, respectively 30 , and the optimum requirements for both vaginal and rectal intercourse cannot be bridged in a single lubricant. Cunha and colleagues commented that 'outcomes of low pH are even less understood, but animal data suggest that values of 3 or less are unacceptable for human use' 39 . Therefore, clinicians need to be aware that some preparations do not meet this recommendation (see Table 1 ).…”
Section: Characteristics To Consider When Choosing a Personal Lubricamentioning
confidence: 99%
“…Although cytotoxic effects associated with hyperosmolar lubricants have been demonstrated in vitro and in humans in several studies 36–38 , a recent study of 12 commercially available lubricants of varying pH and osmolalities failed to find a significant association between these criteria and cytotoxicity 39 . The authors suggested that individual components of the surveyed personal lubricants therefore may have a greater influence on cytotoxicity than pH or osmolality, and added that 'further specific toxicity testing using vaginal microbiota, namely Lactobacillus spp., is advisable' 39 .…”
Section: Characteristics To Consider When Choosing a Personal Lubricamentioning
confidence: 99%
“…The perception by the general population that natural products are safer may account for these observations [ 41 ]. Therefore, more important than complying with the preference for ingredients of natural origin, formulators should be particularly careful with safety aspects of vaginal products [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another nanotechnology-based drug delivery systems are based on liposomes, the first nanoparticles to undergo translation into clinical practice, that are now currently available as marketed formulations, including vaginal preparations to be used as lubricants [170]. These lipid nanoparticles are based on bilayered phospholipid membranes that can be modified by coating with polymers or other molecules for targeted drug release [171].…”
Section: Several Authors Used Mucoadhesive Polymers Such As Eudragit®mentioning
confidence: 99%